HEALTH SECURITY AND THE CHALLENGE OF SOCIAL AND ENVIRONMENTAL VULNERABILITIES IN NIGERIA - Musediq Olufemi Lawal; Rasheed Oyaromade; Akin George Ogunleye; Olawale Olufemi Akinrinde; Young Kenneth Irhue (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
There is a growing recognition of the importance of health security to economic development globally. ‘Health security’ as a phenomenon continues to receive the attention of academics and policymakers in the course of ensuring a state of complete physical, mental and social well-being for all.  Nigeria’s health policy equally gives a premium to this.  The aim of this study, hinging on archival and qualitative research design, is to explore health security in Nigeria vis-à-vis the constraining social and environmental vulnerabilities.  The discourse took into account unfolding social challenges and various environmental problems coupled with the high level of poverty. This article indicates that social and environmental uncertainties interact with many parts of the health care system in a variety of ways. This hurts health security in Nigeria as a result of poor infrastructure development, insufficient government financing, the lack of an integrated system for disease prevention and monitoring, frequent policy reversals, security issues, and unimpressive health indicators. Because of this and considering the state of the Nigerian health care that is worsening on a global standard, it is obvious that health security is yet to have a strong footing.  For health security to have a meaningful impact on people's wellbeing, appropriate health services should be made accessible to those who need them.